A novel strategy for effectively implementing a typical AVC scheme using finite element model updating. Issue 6 (2nd November 2019) - Sood, Poonam; Sharma, Manu; Sharma, Sukesha; Kumar, Navin
Abstract: Finite element (FE) model of a square cantilevered plate instrumented with a piezoelectric sensor and an actuator is created using Hamilton's principle. Rotational degrees of freedom (dofs) of the FE model are eliminated using system equivalent reduction expansion process (SEREP). Experimental mode shapes and natural frequencies are extracted from the structure using high speed cameras and digital image correlation (DIC) technique. Initial FE model is updated using experimental mode shapes and natural frequencies by well-known Berman and Nagy approach. Updated FE model thus derived is further reduced to first three modes using orthonormal modal reduction technique. Modal model of the smart plate is then used to derive state space model of the smart plate. Two Kalman observers are constructed: one using initial FE model and other using updated FE model. Active vibration control experiments are conducted on the cantilevered using these two Kalman observers in the control law. It is observed that much better vibration suppression occurs when Kalman observer based on updated FE model is used in the control law. Strategy suggested in this work to implement a typical active vibration control scheme on a structure is simple and yet very effective.